Architecture Elements of the Lemat Formation of the Lubuk Bernai Region, Batang Asam District, Tanjung Jabung Barat Regency, Jambi Province - Sapto Kis Daryono; Sutanto Sutanto; Carolus Prasetyadi; Eko Teguh Paripurno (Journal of Earth and Marine Technology (JEMT), 2022)
The study of facies analysis and interpretation of the depositional environment of the Lemat Formation located at Bukit Tiga Puluh aims to clarify the problems found in Paleogene sediments in the South Sumatra Basin. A detailed analysis of the fluvial facies has been carried out in the Lubuk Bernai track. A number of observations, profiling, and measured stratigraphic section have been carried out. The stratigraphy of the study area can be divided into 5 units from old to young, namely the Mentulu-metamorphic sandstone unit, Lemat conglomerate unit, Lemat gravel-sandstone unit, Benakat volcanic-siltstone unit, and the alluvial deposit unit. The stratigraphic relationship between Mentulu metamorphic-sandstone unit and Lthe emat conglomerate unit is nonconformity. The relationship between Lthe emat conglomerate unit and Lemat gravel-sandstone unit and Benakat volcanic-siltstone unit is interfingering. The relationship between alluvial deposit units with Lemat conglomerate units and Lemat gravel-sandstone units is aan ngular unconformity. Analysis of lithofacies and architectural elements of the study area showed a fluvial depositional environment. The resulting architectural elements are 8 associations: SG (sedimentary gravity flow), GB (gravel bedform), SB (sandy bedform), CH (channel), DA (downstream accretion), HO (scour-hollow fill), AC (abandoned channel) and FF (overbank fine). The depositional environment of the Lemat Formation; Lemat conglomerate unit in alluvial fans environment, Lemat gravel sandstone unit in the shallow environment, gravel-bed braided river. In the Benakat tuffaceous-siltstone unit, it was deposited in a flashy, ephermal, sheet flood, sand-bed river environment.